Analysis of Morphometric Features and Development of a Regression Model for Predicting the Body Weight of Kuantan Cattle - Zumarni; Andawaty; Misrianti, Restu; Ali, Arsyadi; Fitra, Deni; Djuliyanto, Erik; Safira, Nurul; Aswan, Aswan (Jurnal Ilmu-Ilmu Peternakan, 2023)
The Kuantan cattle, recognized as one of Indonesia's local breeds according to the Indonesian Ministry of Agriculture's Decree Number 1052/Kpts/SR.120/10/2014, were the focus of this study. The objective was to characterize morphometric features, estimate the body weight of Kuantan cattle through regression analysis based on body measurements, and compare the results with the School formula. The research was conducted in Pekanbaru and Kuantan Singingi Regency, using Kuantan cattle from Kuantan Singingi Regency (n=180) and UPT Pasir Putih, Dinas Peternakan dan Kesehatan Hewan, Riau Province (n=30). Morphometric parameters, including wither height, body length, and chest girth, were observed. Descriptive statistics (mean, standard deviation, and coefficient of variation) were used for data analysis. Regression equations were analyzed using SPSS 27. The findings indicated no significant morphometric differences between male and female Kuantan cattle. The body weight of Kuantan cattle could be predicted using single and combined body measurements as predictors. Chest girth (CG) emerged as the best predictor in the regression equation for single body measurement, with the highest values of r (0.98), R2 (0.96), and Adj R (0.95) in males, and r (0.88), R2 (0.78), and Adj R (0.77) in females. In combined predictors, the combination of CG and wither height (WH) yielded the highest values for r (0.99), R2 (0.99), and adj R (0.99) in males, and r (0.92), R2 (0.91), and adj R (0.83) in females. The most accurate prediction of body weight in Kuantan cattle was achieved by combining two body measurements, CG and WH. Using the regression equation for estimating body weight proved to be more accurate than the School formula